2018
DOI: 10.3390/healthcare6010024
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Objective Social Isolation from Family and Friends among Older Adults

Abstract: This study examined the correlates of objective social isolation from extended family members and friends among older adults. The analysis is based on the older adult sub-sample of the National Survey of American Life (n = 1321). Multinomial logistic regression analyses examined race/ethnicity, demographics, functional health and family and friend network factors as correlates of objective isolation from family and friends. Only 4.47% of respondents were objectively isolated from both their extended family and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 41 publications
5
51
1
Order By: Relevance
“…Therein, the results of this study showed that the integrated healthcare program improved the static and dynamic balance among the physical functions of the elderly individuals; increased their ego integration and role self-efficacy; decreased their loneliness; and resulted in the improvement of physical, social, and mental health. The results of this study can be seen as supporting previous studies that demonstrated improved emotional health and self-efficacy through physical activities for the elderly adults with disabilities on the basis of RAM [45], and improved emotional health by reducing loneliness and depression through social support [46].…”
Section: Effect Of the Integrated Healthcare Programsupporting
confidence: 88%
“…Therein, the results of this study showed that the integrated healthcare program improved the static and dynamic balance among the physical functions of the elderly individuals; increased their ego integration and role self-efficacy; decreased their loneliness; and resulted in the improvement of physical, social, and mental health. The results of this study can be seen as supporting previous studies that demonstrated improved emotional health and self-efficacy through physical activities for the elderly adults with disabilities on the basis of RAM [45], and improved emotional health by reducing loneliness and depression through social support [46].…”
Section: Effect Of the Integrated Healthcare Programsupporting
confidence: 88%
“…The mechanism of this finding is not known, and necessitates additional research. Literature has connected social isolation and lack of social support to a wide range of health problems such as depression, chronic disease, and poor self-rated health [95,96,97,98,99]. This finding is important because social isolation is common among AA older adults [96,99].…”
Section: Discussionmentioning
confidence: 99%
“…For people sixty-five and over, living alone is strongly correlated with feeling subjectively lonely (University of Michigan, Institute for Healthcare Policy and Innovation 2019). Ironically, although older people living alone often report loneliness, they have larger social networks and more frequent participation in social activities (Chatters et al 2018). Perhaps, the social connections available to older adults living alone do not generally reflect a preference to share company with someone, but instead the need for professional services.…”
Section: The Proposalmentioning
confidence: 99%
“…For example, connections instituted following the death of a spouse or deterioration of health might reflect a need for transportation or caregiving and might not involve the kinds of social or emotional ties that keep loneliness at bay. While many societies express normative expectations that families will meet older people's affiliative and social needs, in fact, studies of people age fifty-five and over reveal that older age is a reliable indicator of social isolation from family (Chatters et al 2018). According to social convoy theory, people maintain a network of social relationships that escorts them through life, like a convoy or group of fellow travelers on the road of life (Wrzus et al 2013).…”
Section: The Proposalmentioning
confidence: 99%